PENGUATAN LITERASI VISUAL DAN ESTETIKA BAHASA DALAM PEMBUATAN TOTEBAG ECOPRINT BERBASIS KEARIFAN LOKAL DI DESA SELEMAK - Prina Yelly; Iqbal Nuari (Jurnal Pengabdian Masyarakat Indonesia (JPMI), 2025)
The low levels of visual literacy and language aesthetics among the people of Selemak Village hinder the optimal utilization of local potential in creative economic activities. This community service program aims to raise awareness and technical skills among housewives and young women in producing ecoprint tote bags based on local wisdom. The approach used includes Asset-Based Community Development (ABCD) and Focus Group Discussion (FGD), with data collection methods such as observation, semi-structured interviews, and questionnaires. Results show that 87% of participants understood the visual and cultural concepts of ecoprint motifs, and 73% demonstrated improved technical and narrative skills. Participant satisfaction reached a 4.6 out of 5 scale. Despite challenges like limited materials and initial experience, the program successfully enhanced visual literacy, verbal expression, and local creative economic potential through active community participation.